P97 Usefulness of fibre-optic bronchoscopy for the investigation of lung cancer in patients with non-massive haemoptysis and non-diagnostic CT. (11th November 2022) - Navarra, A; Mogal, R
Abstract : Introduction and Objectives: The current practice of investigating patients with non-massive haemoptysis includes a chest radiograph followed by CT thorax. It is a common practice to then perform a fibre-optic bronchoscopy to exclude lung malignancy. In the diagnosis of lung cancer, CT thorax has high sensitivity (88.9%) 1 and very low rate of false negatives (92.6% specificity) 1 . Therefore, bronchoscopy as an additional investigation is unlikely to yield a cancer diagnosis. The aim of this study is to assess the diagnostic rate of bronchoscopy for lung cancer in patients with haemoptysis and normal or non-diagnostic CT scan. Methods: Retrospective review was performed of 274 patients presenting with haemoptysis, from January 2012 to December 2017, who had a CT chest showing findings other than malignancy, or normal and were investigated with fibreoptic bronchoscopy. These cases were again retrospectively reviewed in January 2022, to assess for development of lung cancer in this timeframe. Results: Clinical and demographic characteristics can be found in table 1 . Bronchoscopy was normal in 244 patients (89%). Second most common finding was airway inflammation (n=12, 4%), followed by frank blood or contact bleeding (n=8, 3%), vocal cord polyps (n=4, 1.5%), mucoid secretions (n=3, 1%), and one case each of bronchomalacia (<1%) and segmental narrowing (<1%). Out of 171 bronchial washes sent for cytology, none revealed malignant cells. On review in January 2022, 36 patients (13%) had passed away, 4 of which because of lung cancer. They all had normal investigations including CT and bronchoscopy on initial presentation. Only 21 patients (8%) had experienced further episodes of haemoptysis. Of these, 1 patient had been found to have lung cancer, 3 years after initial investigations which were normal. Conclusions: Fibre-optic bronchoscopy is extremely unlikely to diagnose lung malignancy in patients with a normal or non-diagnostic CT for lung cancer. We suggest a prospective study to evaluate this further and will help to avoid unnecessary bronchoscopy procedures. References: Toyoda Y, Nakayama T, Kusunoki Y, Iso H, Suzuki T. Sensitivity and specificity of lung cancer screening using chest low-dose computed tomography. Br J Cancer . 2008 May.